Impact of Oil Prices and Stock Returns: Evidence of Oil and Gas Mining Companies in Indonesia during the COVID-19 Period - Suripto, Suripto; Supriyanto, Supriyanto; Sugiono, Arif; Sari, Putri Irmala (International Journal of Energy Economics and Policy, 2021)
This study points to analyze the determinants of stock return revelation in oil and gas mining division companies recorded on the Indonesia Stock Trade-in 2019-2021 amid the Covid 19 emergency. The think about utilized the Eviews Program as information preparing and the irregular impact relapse show was chosen to look at the relationship between outside and inside markers as autonomous factors counting Current Ratio (CR), debt to equity ratio (DER), total asset turnover (TATO), return on assets (ROA), oil price (WTI), an exchange rate (FOREX), institutional ownership (IO). The comes about appeared that the current proportion, obligation to value ratio, and add up to resource turnover did not influence stock returns. Return on resources, exchange rates, and institutional ownership has a negative and significant impact on stock returns, while oil prices have a positive and widespread effect on stock returns. Keywords: Oil Price, Stock Return, Probability, Institutional Ownership, Covid-19 JEL Classifications: E22, E44, G11, O42, Q47 DOI: https://doi.org/10.32479/ijeep.11290